HUBUNGAN KAUSALITAS ANTARA MONEY SUPPLY DAN INDEKS HARGA SAHAM GABUNGAN : SEBUAH PENELITIAN EMPIRIS PADA TAHUN 2016-2023 DALAM KERANGKA TEORI KEYNESIAN - Setiawan, Agung; Auliya Nisa Ramadina; Dewi, Fatma; Nurikmah, Julia (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
This research aims to analyze the causal relationship between the Money Supply (JUB) and the Composite Stock Price Index (IHSG) in Indonesia in the 2016-2023 period. The method used in this research is the Vector Error Correction Model (VECM) to estimate data that is not stationary but has a cointegration relationship. Secondary data was obtained from bps.go.id for 8 years. The results of the analysis show that there is no causal relationship between JUB and IHSG, but there is a one-way relationship where JUB can influence IHSG positively. The implication of this research is the importance of careful monitoring and management of the Money Supply to prevent negative impacts such as inflation which can disrupt economic growth. This research is expected to provide new insights and facilitate future decision making regarding the relationship between JUB and IHSG in the Indonesian financial market.